EFFECTS OF BRAND PERSONALITY DIMENSIONS AND SELF-CONGRUITY ON REVISIT INTENTION: A STRUCTURAL EQUATION MODELING APPROACH - Shaohua Yang; Salmi Mohd Isa; T. Ramayah; Nik Nur Azhani Anuar; Ramona Blanes, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The study is aimed to test the structural relationship between brand personality dimensions, selfcongruity (i.e., actual and ideal self-congruity) and revisit intention. Brand personality was conceptualised as a five-dimensional construct including sincerity, excitement, competence, sophistication, and ruggedness. When Chinese outbound tourists perceived various personality traits of destination brand, it might influence their revisit intentions to Glasgow, UK. The current study proposed that self-congruity exerted mediating effects between five dimensions of brand personality and revisit intention. Structural equation modelling was applied to confirming the hypothesis testing. Findings of current study suggested that only two dimensions (sincerity and excitement) had an indirect impact on revisit intention through ideal self-congruity. Furthermore, this study contributed to the extant literature by partially confirming self-congruity theory in the setting of Glasgow tourism. Research findings are also beneficial to destination marketing organisations (DMOs) in their efforts to make Glasgow destination attract more repeated Chinese tourists.